Separation of Methanol-Toluene Azeotropic Mixture by Extractive Distillation - Tang, Ke; Bai, Peng; Zhang, Jinwei; Huo, Yi (Asian Journal of Chemistry, 2012)
Methanol and toluene formed a minimum azeotrope and extractive distillation should be a suitable method to separate their mixture. In this work, a systematic study of the separation of methanol-toluene mixture with an entrainer by extractive distillation was performed. o-Xylene was chosen to be the entrainer because it could break the original binary azeotrope. Vapour-liquid equilibrium (VLE) of methanol-toluene-o-xylene system was determined experimentally and NRTL model was the most suitable one to predict this system. The feasibility analysis of this process was validated by simulation through chemical process simulation software-Aspen Plus and the optimal operating conditions of the extractive distillation process were valuable for industrial applications. Simulation results were then corroborated in a batch experimental packing column. In both the simulation and experiments, methanol and toluene, whose purity is more than 99.5 %, were obtained respectively.